KNOWLEDGE, ATTITUDE AND PRACTICE OF POLIO PREVENTION AMONG PEOPLE IN KHYBER PAKHTUNKHWA: KAP of Polio Prevention - Mehmood, Talat; Babar, Ayesha (Pakistan Armed Forces Medical Journal, 2014)
Objectives: To assess the knowledge, attitude and practice of Polio among people in Khyber Pakhtun Khwa and to recommend measures in order to improve the awareness of disease. Study Design: Descriptive cross sectional study. Place and Duration of Study: This study was conducted at CMH Nowshera, CMH Mardan and Kohat General Hospital from March to June 2013. Subjects and Methods: Persons presenting for consultation to tertiary care hospitals at medical reception rooms were approached by convenience sampling. Structured questionnaire was developed and data was collected by interviews. Results: The findings of the study revealed that out of 296 persons participated in study 57.4% were males while 42.2% were females. They were residents of Mardan, Nowshera, Kohat and Swabi districts of Khyber Pakhtukhwa. Persons who believed that vaccine is prohibited in religion were 13.9%, 81.1% persons knew about Polio disease and 84.5% persons believed that disease could be prevented by giving vaccines to children. Persons who gave vaccine to their children were 88.9% and 66.9% also knew the schedule of the vaccine. Pressure groups which included tribal elders’ stopped 19.3% people from giving vaccine to their children and for 11.1% persons the facility of giving vaccine was not available. Persons who believed that Polio can cause infertility were 11.5% and 20.9% believed that Polio vaccine cannot prevent Polio disease. Persons who have seen patient of Polio were 38.9% and 88.5 % persons wanted to eradicate disease from Pakistan. Conclusion: The results of the study revealed that people have adequate knowledge about Polio and wanted to eradicate it from Pakistan by participating in vaccination activities but still there are few people who believe that Polio vaccine cannot prevent disease resulting in failure to adminster vaccine for their children.